Sensors, Medical Images and Signal Processing: - Depeursinge, A.; Müller, H.; Section Editors for the IMIA Yearbook Section on Sensor, Signal, and Imaging Informatics (Yearbook of Medical Informatics, 2009)
Objectives To summarize current excellent research in the field of medical sensor, signal and imaging informatics.Method Synopsis of the articles selected for the IMIA (International Medical Informatics Association) Yearbook 2009.Results Current research in the field of sensors, signal, and imaging informatics is characterized by theoretically sound techniques and evaluations with focus in imaging informatics.Conclusions The best paper selection of articles on sensors, signal, and imaging informatics shows examples of excellent research on methods concerning theoretically sound original development in this field. Imaging and particularly multi-dimensional imaging has had in 2008 by far the largest number of publications compared to signals and sensors.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; image processing; signal processing; medical sensors